2019
DOI: 10.1016/j.jflm.2019.06.001
|View full text |Cite
|
Sign up to set email alerts
|

The experiences of sexually assaulted people attending Saint Mary's Sexual Assault Referral Centre for a forensic medical examination

Abstract: This study aims to explore the experiences of people who have attended Saint Mary's Sexual Assault Referral Centre (SARC) for a forensic medical examination (FME). Within the United Kingdom, SARCs support complainants following a sexual assault, delivering specialised care and gathering medico-legal evidence for court proceedings. To date, there has been limited research evaluating SARCs responses towards complainants. 863 Feedback and Evaluation forms, from a three-year period, completed by clients who access… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 8 publications
0
12
1
1
Order By: Relevance
“…Only four of the papers included men as participants (and there were only small numbers in comparison to women participants in those studies) (Lovett et al, 2004;Majeed-Ariss et al, 2019;Miyamoto et al, 2021;Peeters et al, 2019) and only one paper had any representation from participants identifying as nonbinary (Miyamoto et al, 2021). There is no indication in any of the papers of the participants' sexuality except that one quoted interview subject, in the report by Lovett et al, is referred to as a gay man.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Only four of the papers included men as participants (and there were only small numbers in comparison to women participants in those studies) (Lovett et al, 2004;Majeed-Ariss et al, 2019;Miyamoto et al, 2021;Peeters et al, 2019) and only one paper had any representation from participants identifying as nonbinary (Miyamoto et al, 2021). There is no indication in any of the papers of the participants' sexuality except that one quoted interview subject, in the report by Lovett et al, is referred to as a gay man.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, one of the patients in Majeed-Ariss' patient survey voiced how the positive experience of the forensic examination in some ways countered the negative experience of the sexual assault, I would just like to say, that following on from such a traumatic experience, I have now experienced, a caring, helpful, meaningful experience. (Majeed-Ariss et al, 2019) Further one paper also reported that 74% of patients agreed the examination "helped them feel better," although 4% strongly disagreed (Miyamoto et al, 2021).…”
Section: Choice and Controlmentioning
confidence: 99%
“…In cases in which this policy cannot be realized, an appropriate training of all staff addressing established standards, i.e. showing a professional attitude towards sexual assault issues and treating victims with dignity, sensitivity and without prejudice should be emphasized (16,18). Chowdhury-Hawkins et al argue that the women with a lack of sex preference (comparable with the respondents in our study answering with "neutral") might want to undertake the examination as quickly as possible due to the previous emotional trauma so that they would tolerate whatever is involved to achieve that.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, research addressing the victim's individual perception of FME is scarce. Existing data were collected in care settings differing from ours, assessed different study populations or used other methodological designs such as semi-structured interviews (16)(17)(18). Most of the previous research focused on retrospective characterization of patient populations (19)(20)(21)(22), perception of healthcare providers themselves of the examination process (23)(24)(25), or results and legal implications derived from the FME itself (26,27).…”
Section: Forensic Medical Examination After Sexual Violencementioning
confidence: 99%
“…Approximately 100,000 US women present for emergency care after SA each year, 2 yet opportunities to gain insights into the lives of women who present for emergency care after sexual assault (SA) are limited, both because such women rarely return for care or self‐identify when receiving further care, 3–5 and because few studies have assessed the life experiences of women SA survivors after SA nurse examiner (SANE) care. Qualitative studies of SA have focused largely on the receipt of health care services, 7–11 with less attention paid to survivors’ broader life experiences.…”
Section: Introductionmentioning
confidence: 99%